2009
DOI: 10.1159/000229784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on Combined Therapy of Botulinum Toxin Injection and Small Balloon Dilation in Patients with Esophageal Achalasia

Abstract: Background and Study Aims: To compare the efficiency of pneumatic balloon dilation, botulinum toxin (BT) injection, and the combination of the two modalities in the management of esophageal achalasia. Patients and Methods: Ninety patients with esophageal achalasia were randomly divided into three groups according to different interventions, i.e. patients in group A received 100 U BT injection; patients in group B were given balloon dilation, and patients in group C were subjected to balloon dilation plus 100 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…50,51 However, although multiple trials have demonstrated short-term benefits of botulinum toxin injection, a single injection of botulinum toxin has only short-duration clinical effects with relapses within several months occurring frequently. [51][52][53][54][55][56][57][58][59] Typically, 100 U of botulinum toxin is injected into 4 quadrant of LES each as 4 divided doses. There is wide variability in the timing of the botulinum toxin injections.…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%
“…50,51 However, although multiple trials have demonstrated short-term benefits of botulinum toxin injection, a single injection of botulinum toxin has only short-duration clinical effects with relapses within several months occurring frequently. [51][52][53][54][55][56][57][58][59] Typically, 100 U of botulinum toxin is injected into 4 quadrant of LES each as 4 divided doses. There is wide variability in the timing of the botulinum toxin injections.…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%
“…When PD is performed after myotomy, it has only a 50% response but no higher risk for complications. PD after BoTox injection is safe and feasible but there is no added benefit to combination therapy of BoTox injection before pneumatic dilation 24 …”
Section: Endoscopic Therapies For Achalasiamentioning
confidence: 99%
“…11 and 12). Randomized studies of the two procedures have tended to favor the surgical treatment also, although the largest trial mounted to date at very early follow‐up suggests there is not a lot to choose between the two therapies 24 …”
Section: Surgical Therapymentioning
confidence: 99%
See 2 more Smart Citations